Electroless Deposition of Silver onto Alumina Substrates (The Minerals, Metals and Materials Society, 1998)
Silver has the highest electrical conductivity of all metals and consequently this property is an attractive feature which makes it a leading candidate for use in electronic devices. The research conducted was focused primarily on the development of a process for obtaining a deposited silver-coating onto alumina, for applications related to electrical-conducting devices and, ancillarily, catalysts. Alumina balls and plane substrates were utilized for the investigation. The coating process employed an aqueous arnmoniacal silver-nitrate electrolytes with a formaldehyde solution as the reductant. Modifying additives - an activator which would be expected to promote good deposition-characteristics onto the (dielectric) substrate and an inhibitor which would obviate homogeneous reduction (precipitation) of silver was observed when the activator-containing silver-electrolyte reductant constituents were combined. However, the silver-electrolyte/reductant system with inhibitor could be employed (at 80°C) to achieve a viable (subject to future research optimization) coating on alumina. The influence of the processing temperature on the deposition process was delineated during the course of the research. The morphology of the deposited-silver on the alumina balls was assessed by SEM imaging. A tape-peel test was employed, with the plane substrates, to semi-quantitatively characterize the adhesion to the alumina.